Regulatory T cell homing and activation is a signature of neonatal sepsis - Sossou, Darius; Ezinmegnon, Sem; Agbota, Gino; Gbedande, Komi; Accrombessi, Manfred; Massougbodji, Achille; d’Almeida, Marceline; Alao, Jules M.; Dossou-Dagba, Ida; Pachot, Alexandre; Vachot, Laurence; Brengel-Pesce, Karen; et al. (Frontiers in Immunology, 2024)
Regulatory T cells (Treg) play a prominent role in utero tolerating non-inherited maternal antigens and in regulating immune responses against pathogens at birth. This study investigates Treg immunity in newborns in West Africa, where sepsis remains a major public health problem. Treg phenotypes on neonates subgroups with early-onset sepsis (EOS), presumed sepsis, and healthy newborn with and without prenatal risk factors were evaluated. Treg phenotypes varied according to prenatal conditions, with increase in Treg frequency and Foxp3 expression in healthy newborns with prenatal risk factors compared to those with none risk. Compared to healthy newborns with prenatal risk factors, EOS neonates had a significantly reduced frequency of Treg and Foxp3 expression. In the Treg pool, higher frequency of activated Treg was observed in EOS neonates, suggesting an in-utero activation upstream of the sepsis onset. Their migration to the infection site may explain the reduced frequency of circulating Integrin α4β1 + Treg suggestive of homing to the endothelial tissue. EOS neonates show increases expression of CTLA-4, PD-1 and CD39 on Treg, which negatively regulate the activation of effector T cells (Teff) corroborating by the lower frequency of Teff in EOS neonates. The higher frequency of CD39 + Treg and the lower frequency of integrinα4β1 + Treg in EOS nonsurvivor suggests that Treg exhaustement and endothelial homing are associated with outcome severity. Neonates developing EOS are born with an altered Treg phenotypic profile. Treg expression of CTLA-4, PD-1, CD39, and integrinα4β1 cell markers can be considered as early warning or diagnostic markers of EOS.